Somatic mutation detection and KRAS amplification in testicular germ cell tumors - Cabral, Eduardo R. M.; Pacanhella, Marilia F.; Lengert, Andre V. H.; Reis, Mariana B. dos; Leal, Leticia F.; Lima, Marcos A. de; Silva, Aline L. V. da; Pinto, Icaro A.; Reis, Rui M.; Pinto, Mariana T.; Cárcano, Flavio M. (Frontiers in Oncology, 2023)
Background Testicular Germ Cell Tumors (TGCT) are the most common cancer among young adult men. The TGCT histopathology is diverse, and the frequency of genomic alterations, along with their prognostic role, remains largely unexplored. Herein, we evaluate the mutation profile of a 15-driver gene panel and copy number variation of KRAS in a large series of TGCT from a single reference cancer center. Materials and methods A cohort of 97 patients with TGCT, diagnosed at the Barretos Cancer Hospital, was evaluated. Real-time PCR was used to assess copy number variation (CNV) of the KRAS gene in 51 cases, and the mutation analysis was performed using the TruSight Tumor 15 (Illumina) panel (TST15) in 65 patients. Univariate analysis was used to compare sample categories in relation to mutational frequencies. Survival analysis was conducted by the Kaplan–Meier method and log-rank test. Results KRAS copy number gain was a very frequent event (80.4%) in TGCT and presented a worse prognosis compared with the group with no KRAS copy gain (10y-OS, 90% vs. 81.5%, p = 0.048). Among the 65 TGCT cases, different variants were identified in 11 of 15 genes of the panel, and the TP53 gene was the most recurrently mutated driver gene (27.7%). Variants were also detected in genes such as KIT, KRAS, PDGFRA, EGFR, BRAF, RET, NRAS, PIK3CA, MET, and ERBB2, with some of them potentially targetable. Conclusion Although larger studies incorporating collaborative networks may shed the light on the molecular landscape of TGCT, our findings unveal the potential of actionable variants in clinical management for applying targeted therapies.